2022
DOI: 10.17275/per.22.84.9.4
|View full text |Cite
|
Sign up to set email alerts
|

Bibliometric Profile of an Emerging Journal: Participatory Educational Research

Abstract: Participatory Educational Research (PER)" journal is one of the journals that contributes to the field of education and indexed in major international databases such as ERIC and Scopus. This study provides the bibliometric characteristic of the total 347 articles published in PER during the period of 2014-2021 using bibliometric analysis. Publish or Perish software to collect citation data from Google Scholar was used as an analysis instrument for the impact of the articles. It was found that short-titled arti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Therefore, the finding obtained in this study in terms of the number of authors is in harmony with the studies in the international literature. is regarded prestigious in academia, and it is a natural byproduct of supply and demand (Arslan et al, 2022;Huang, 2016). A Total of 414 citations from WoS were made to the studies published in the journal between 2014 and 2021.…”
Section: Results and Discussion For Rq1mentioning
confidence: 99%
“…Therefore, the finding obtained in this study in terms of the number of authors is in harmony with the studies in the international literature. is regarded prestigious in academia, and it is a natural byproduct of supply and demand (Arslan et al, 2022;Huang, 2016). A Total of 414 citations from WoS were made to the studies published in the journal between 2014 and 2021.…”
Section: Results and Discussion For Rq1mentioning
confidence: 99%
“…As previously stated in prior research (Arslan et al, 2022), bibliometric data change over time with each publication. As a result, it is suggested that the authors consider the topicality in future studies.…”
Section: Conclusion and Future Rese Archmentioning
confidence: 85%